Evolution of Citrus Disease Management Programs and Their Economic Implications: The Case of Florida’s Citrus Industry - Ariel Singerman; Marina Burani Arouca (EDIS, 2017)
This article focuses on the costs of managing exotic citrus diseases as they become endemic or established within a citrus industry, and Florida is used as an example. In particular, the figures in this article represent the cost of production for processed juice oranges in the Southwest Florida region and fresh market grapefruit in the Indian River region.